Endoscopic biliary stenting: indications, choice of stents, and results: European Society of Gastrointestinal Endoscopy (ESGE) clinical guideline : updated October 2017 - Dumonceau, Jean-Marc; Tringali, Andrea; Papanikolaou, Ioannis S.; Blero, Daniel; Mangiavillano, Benedetto; Schmidt, Arthur; Vanbiervliet, Geoffroy; Costamagna, Guido; Devière, Jacques; García-Cano, Jesús; Gyökeres, Tibor; Hassan, Cesare; et al. (Endoscopy, 2018)
ESGE: recommends against routine preoperative biliary drainage in patients with malignant extrahepatic biliary obstruction; preoperative biliary drainage should be reserved for patients with cholangitis, severe symptomatic jaundice (e. g., intense pruritus), or delayed surgery, or for before neoadjuvant chemotherapy in jaundiced patients. Strong recommendation, moderate quality evidence. ESGE: recommends the endoscopic placement of a 10-mm diameter self-expandable metal stent (SEMS) for preoperative biliary drainage of malignant extrahepatic biliary obstruction. Strong recommendation, moderate quality evidence. ESGE: recommends SEMS insertion for palliative drainage of of extrahepatic malignant biliary obstruction. Strong recommendation, high quality evidence. ESGE: recommends against the insertion of uncovered SEMS for the drainage of extrahepatic biliary obstruction of unconfirmed etiology. Strong recommendation, low quality evidence. ESGE: suggests against routine preoperative biliary drainage in patients with malignant hilar obstruction. Weak recommendation, low quality evidence.ESGE: recommends uncovered SEMSs for palliative drainage of malignant hilar obstruction. Strong recommendation, moderate quality evidence.ESGE: recommends temporary insertion of multiple plastic stents or of a fully covered SEMS for treatment of benign biliary strictures. <break/>Strong recommendation, moderate quality evidence. ESGE: recommends endoscopic placement of plastic stent(s) to treat bile duct leaks that are not due to transection of the common bile duct or common hepatic duct. Strong recommendation, moderate quality evidence.